Challenges and Urgency of Character Education for Children in the Modern Era - Reisa Aulia Fatimah; Rahman Wahid; Citera Yusrina (CV. Ksatria Siliwangi, 2024)
In this modern era, digitization has become a supporting factor in globalization. Digitization is a rapidly developing technology that allows information to spread easily. In practice, technology does not always bring positive things; many children are beginning to be indoctrinated with various negative things from this technological development. In this situation, there are also various challenges to forming good character values in children. This study uses a qualitative research method with a library research approach. The data collection technique is a literature study that compiles various sources relevant to the research topic. Conceptually, character education is an effort made on children from an early age so that they get used to doing good things and stay away from despicable traits. The goal is for children to become individuals who are faithful, moral, knowledgeable, and understand existing rules and norms. This goal is in line with Law No. 20 of 2003. The challenges of character education for children in the modern era are the development of technology, social change, identity crisis and value disorientation, the role of family and environment, and challenges at school. Given these challenges, character education is urgent because children may be exposed to various negative influences if they are not given character education and strict supervision, one of which is becoming temperamental. The purpose of this study is to provide an understanding of character education in children and to raise awareness to minimize challenges related to character education in children.